The Impact of Using Brisk Walking Exerrcise in Lower Blood Sugar of Patients with Type 2 Diabetes Mellitus - Kasmad Kasmad; Awaludin Jahid Abdillah; Mila Karnelia (Qualitative and Quantitative Research Center, 2022)
The stability of blood sugar levels in people with diabetes mellitus is still difficult to control because of the patient's lack of awareness to do physical activity. This study aimed to determine the impact of brisk walking exercise on reducing blood sugar levels in patients with type II diabetes mellitus. This study used a quasi-experimental design with a non-equivalent control group design approach. The population in this study were patients with type 2 DM in the working area of ​​the Luragung Health Center, Kuningan Regency. The sample taken in this study was 28 respondents using the purposive sampling technique. The statistical test used was the Wilcoxon test. The results showed that the respondents' blood sugar levels before brisk walking were 200-250 ml/dl. After brisk walking, there was a decrease in blood sugar levels, which were tested using the Wilcoxon statistical test resulting in a p-value of 0.01<0.05, meaning Ha was accepted. The conclusion of this study is the impact of brisk walking exercise on reducing blood sugar levels in patients with type 2 diabetes mellitus in the working area of ​​the Luragung Health Center. It is hoped that people with type 2 diabetes mellitus get used to doing physical activities or sports to help control blood sugar levels.